Translanguaging in scientific practices: a study of high school teachers in English Medium Instruction inquiry-based science classrooms - Lu, Chaoqun; So, Winnie Wing Mui (International journal of science education, 2023)
English as a Medium of Instruction (EMI) is being used to teach academic subjects in international programmes in China to meet the growing number of Chinese students' need to study abroad. Through the lens of inquiry-based science teaching, this study examined how the four EMI science teachers of an international programme at a private high school employed translanguaging in scientific practices such as identifying variables and formulating hypotheses. Based on the data collected from a case study, the analyses demonstrate how these science teachers used multilingual and multimodal resources to facilitate students' engagement in scientific inquiry activities and to promote the construction of scientific knowledge. A total of seven types of translanguaging practices were identified, including opening the inquiry, negotiating directions, teacher encouragement, managing discipline, fun learning environment, definitions, and explanations. The findings imply that pedagogical translanguaging can create a space for the construction of scientific knowledge, as well as a space for the implementation of scientific practices in an inquiry-based EMI classroom environment.